Nonlinear Model Predictive Control strategy for steam turbine rotor stress. (February 2019) - Dettori, S.; Maddaloni, A.; Colla, V.; Toscanelli, O.; Bucciarelli, F.; Signorini, A.; Checcacci, D.
Abstract: The paper proposes a Nonlinear Model Predictive Control strategy for the control of steam turbines rotor thermal stresses, which exploits the approximation of the turbine rotor as an infinite cylinder subjected to external convection. The Nonlinear Model Predictive Control allows optimizing the control strategy in the long term, by significantly reducing the machine start-up time during the power up ramp. This study proposes two different control strategies: the former one is based on the control of the Heat Transfer Coefficient, correlated to the inlet valve stroke. The latter one is based on the control of Heat Transfer Coefficient and the boiler steam temperature reference. Both strategies achieve good results in shortening the start-up time. The overall approach is validated and currently under development on Programmable Logic Controller platforms to the aim of code optimization.